Engineering D-Amino Acid Containing Collagen Like Peptide at the Cleavage Site of Clostridium histolyticum Collagenase for Its Inhibition - Velmurugan, Punitha; Jonnalagadda, Raghava Rao; Unni Nair, Balachandran (PLOS ONE, 2015)
Collagenase is an important enzyme which plays an important role in degradation of collagen in wound healing, cancer metastasis and even in embryonic development. However, the mechanism of this degradation has not yet been completely understood. In the field of biomedical and protein engineering, the design and development of new peptide based materials is of main concern. In the present work an attempt has been made to study the effect of DAla in collagen like peptide (imino-poor region of type I collagen) on the structure and stability of peptide against enzyme hydrolysis. Effect of replacement of DAla in the collagen like peptide has been studied using circular dichroic spectroscopy (CD). Our findings suggest that, DAla substitution leads to conformational changes in the secondary structure and favours the formation of polyproline II conformation than its L-counterpart in the imino-poor region of collagen like peptides. Change in the chirality of alanine at the cleavage site of collagenase in the imino-poor region inhibits collagenolytic activity. This may find application in design of peptides and peptidomimics for enzyme-substrate interaction, specifically with reference to collagen and other extra cellular matrix proteins.